PENGGUNAAN MODUL PIL (PHYSICS, I’M IN LOVE) DALAM PEMBELAJARAN KONSEP CAHAYA DAN ALAT OPTIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS VIII SMP NEGERI 8 PEKANBARU - Desri, Rahmania; Nasir, Muhammad; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research was to describe the improvement of cognitive science learning outcomes of Physics through the application of PIL module (Physics, I'M In Love). The type of this research used Quasi Experimental with in the form of Nonequivalent Control Group Design design. The sample of the research was the students of class VIII 1 as the experimental class and the students of class VIII 4 as the control class. Test of cognitive learning outcomes was use to obtain the data by given to the sample as pretest and postest. Descriptive and inferential analysis were use to analyse the data. The results showed that students' average ability (daya serap) rate by the application of PIL module was better than conventional teaching method. Thus, it can be concluded that the application of PIL module can improve student learning outcomes in physics science lesson in light and optical instrument material at SMP Negeri 8 Pekanbaru.Keywords: PIL Module, Cognitive Learning Outcomes